The use of convolutional coding to reduce bit error rate in CDMA /cNorhayati Mohamad Noor - 202400 Norhayati Mohamad Noor (Skudai: Universiti Teknologi Malaysia, 2001)
Thesis (Master of Engineering (Electrical)) - Universiti Teknologi Malaysia, 2001